The Influence Of Peer Environment And Learning Motivation On Student Interest In Continuing Studies To Higher Education - Fahry Muhamad Shobirin; Iyan Setiawan; Rani Tania Pratiwi (THE PRESTISE, 2026)
This study investigates how peer environment and learning motivation influence students' interest in pursuing higher education at SMA Negeri 1 Ciniru, Kuningan Regency. The research was motivated by school tracer study data revealing that a substantial majority of recent graduates entered the workforce immediately after graduation rather than continuing to universities or colleges. This pattern suggests potential barriers or influences affecting students' educational decision-making processes. Through a quantitative survey methodology, the study examined eleventh-grade students selected via purposive sampling techniques. A structured Likert-scale questionnaire administered through Google Forms assessed students' peer environment characteristics, learning motivation levels, and intentions regarding higher education. Rigorous statistical analysis using multiple linear regression in SPSS included comprehensive validity testing, reliability assessment, and verification of regression assumptions. Both simultaneous and partial hypothesis testing procedures were employed to examine the relationships among variables. Results indicated significant positive influences of both peer environment and learning motivation on students' higher education interest, with learning motivation exhibiting the stronger relationship. The findings have important practical implications, suggesting that educational interventions should prioritize enhancing intrinsic learning motivation while simultaneously fostering positive peer dynamics. Schools should implement career guidance programs, peer mentoring initiatives, and motivational enhancement strategies to improve higher education enrollment rates among graduates.